The Effect of Patient Acuity Tool on Patient Clinical Practicum Assignments on Nursing Student Satisfaction Levels: A Quasi-Experimental Study - Marionne Leigh V. David; Reeanz Arvin V. Bano; Eric Ferdinand S. Joven; Noel Robertino Manansala; Michaella G. Sta. Ana; Ria Valerie D. Cabanes; Mildred G. Glinoga (JKP (Jurnal Keperawatan Padjajaran), 2021)
Background: Unequal patient assignment is a problem of nursing students during clinical practicum. Registered nurses use patient acuity to ensure balanced work distribution, but its benefits has not been assessed on student nurses to date.